Социјалните расходи – предизвик за фискалната одржливост - Tashevska, Biljana; Makreshanska mladenovska, Suzana (Македонска академија на науките и уметностите, 2023)
Social expenditures have been on the rise over the past decades, particularly in developed countries. The average public social spending rose from 11% of GDP in 1970 to 21% of GDP in 2022 across the OECD, with most of the social expenditure devoted to pensions and health care. While social welfare is intended to protect the public against vulnerabilities in life (old age, unemployment, sickness and poverty), social spending is often blamed for the rise in government expenditures and public debt in advanced economies, for dominating public expenditures and crowding-out other productive expenditures. This raises questions about whether existing social welfare programs are sustainable and about the need for adjustments to accommodate the predicted growth of old-age related expenditures amidst adverse demographic trends. However, social expenditures tend to be quite resilient to reduction. One of the most complex challenges is to reconcile the commitments to welfare provision with economic and fiscal pressures that threaten fiscal sustainability. This also applies to the Republic of North Macedonia, as population ageing and the notable emigration of young people pose significant challenges for maintaining fiscal sustainability via rising social expenditures and declining government revenues. This paper focuses on the size, dynamics and structure of social expenditures in the European Union and in the Republic of North Macedonia. This will provide some insight into the potential risks to fiscal sustainability from rising social expenditures that can be useful to policy makers in creating future policies for addressing this issue.
Social expenditures - a challenge to fiscal sustainability
Keywords: социјални расходи (social expenditures); фискална одржливост (fiscal sustainability); демографски предизвици (demographic challenges)